CTX phage of Vibrio cholerae: Genomics and applications. (29th February 2020) - Pant, Archana; Das, Bhabatosh; Bhadra, Rupak K.
Abstract: The bipartite genome of Vibrio cholerae is divided into two circular non-homologous chromosomes, which harbor several genetic elements like phages, plasmids, transposons, integrative conjugative elements, and pathogenic islands that encode functions responsible for disease development, antimicrobial resistance, and subsistence in hostile environments. These elements are highly heterogeneous, mobile in nature, and encode their own mobility functions or exploit host-encoded enzymes for intra- and inter-cellular movements. The key toxin of V. cholerae responsible for the life-threatening diarrheal disease cholera, the cholera toxin, is coded by part of the genome of a filamentous phage, CTXϕ. The replicative genome of CTXϕ is divided into two distinct modular structures and has adopted a unique strategy for its irreversible integration into the V. cholerae chromosomes. CTXϕ exploits two host-encoded tyrosine recombinases, XerC and XerD, for its integration in the highly conserved dimer resolution site ( dif ) of V. cholerae chromosomes. CTXϕ can replicate only in the limited number of Vibrio species. In contrast, the phage integration into the bacterial chromosome does not rely on its replication and could integrate to the dif site of large numbers of gram-negative bacteria. Recent pangenomic analysis revealed that like CTXϕ, the bacterial dif site is the integration spot for several other mobile genetic elements such as plasmids and genomic islands. In this review we discuss about current molecular insights into CTXϕ genomics and its replication and integration mechanisms into hosts. Particular emphasis has been given on the exploitation of CTXϕ genomics knowledge in developing genetic tools and designing environmentally safe recombinant live oral cholera vaccine strains.